2020
DOI: 10.1093/cid/ciaa1558
|View full text |Cite
|
Sign up to set email alerts
|

The Household Secondary Attack Rate of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2): A Rapid Review

Abstract: Background Although much of the public health effort to combat COVID-19 has focused on disease control strategies in public settings, transmission of SARS-CoV-2 within households remains an important problem. The nature and determinants of household transmission are poorly understood. Methods To address this gap, we gathered and analyzed data from 22 published and pre-published studies from 10 countries (20,291 household cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
102
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 26 publications
22
102
10
1
Order By: Relevance
“…High estimated SARs are also in line with observations from surveillance data and cluster reports that the household is the most frequently reported setting of infection [26]. Our study differs from earlier household studies for SAR-CoV-2 in that we observed substantially higher SARs [11, 27]. In fact, only a few studies reported estimates that were somewhat similar to our estimates (32%-38% vs 43%) [28, 29].…”
Section: Discussionsupporting
confidence: 89%
“…High estimated SARs are also in line with observations from surveillance data and cluster reports that the household is the most frequently reported setting of infection [26]. Our study differs from earlier household studies for SAR-CoV-2 in that we observed substantially higher SARs [11, 27]. In fact, only a few studies reported estimates that were somewhat similar to our estimates (32%-38% vs 43%) [28, 29].…”
Section: Discussionsupporting
confidence: 89%
“…As stated in the survey questionnaire [ 1 ], we collected only information concerning the number of total and positive TX patients at the center level and not their individual data, such as transplant history, blood chemistry and immunosuppressive therapy. Nonetheless, it can be argued that any person, be they immunocompetent or immunosuppressed, who comes into contact with a formerly unknown virus has the same susceptibility to the infection, but the consequences are likely to be more severe in immunosuppressed organ transplant recipients [ 26 ]. The preliminary evidence reviewed by Thng [ 27 ] supports this hypothesis, although further prospective studies are needed to provide conclusive data.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the methodological quality and risk of bias of included studies of SARS-CoV-2, we used the same modified version of the Newcastle-Ottawa quality assessment scale for observational studies used by Fung et al . 10 , 11 Studies received as many as 9 points based on participant selection (4 points), study comparability (1 point), and outcome of interest (4 points). Studies were classified as having high (≤3 points), moderate (4-6 points), and low (≥7 points) risk of bias.…”
Section: Methodsmentioning
confidence: 99%